2011
DOI: 10.1099/mic.0.041038-0
|View full text |Cite
|
Sign up to set email alerts
|

Using extracellular polymeric substances (EPS)-producing cyanobacteria for the bioremediation of heavy metals: do cations compete for the EPS functional groups and also accumulate inside the cell?

Abstract: Many cyanobacteria produce extracellular polymeric substances (EPS) mainly of polysaccharidic nature. These EPS can remain associated to the cell surface as sheaths, capsules and/or slimes, or be liberated into the surrounding environment as released polysaccharides (RPS). The ability of EPS-producing cyanobacteria to remove heavy metals from aqueous solutions has been widely reported in the literature, focusing mainly on the biotechnological potential. However, the knowledge of the effects of the metals in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(69 citation statements)
references
References 55 publications
4
64
0
Order By: Relevance
“…6 Venn drawing showing the detected bacterial genera found in the three different groups of H, M, and C. Overlaps between the groups are indicated by the arrangement of the circles is tripled in group M. Moreover, Thiobacillus relative abundance had close relationship with Fe content (R 2 =0.691, P<0.05). In addition, most Cyanobacteria can produce extracellular polymeric substances, mainly polysaccharide, which could adsorb heavy metals dispersed in the environment (Pereira et al 2009(Pereira et al , 2011. In this study, Cyanobacteria was a rare group, but its total read abundances in groups H (795 reads) and M (1202 reads) were significantly higher than in group C (92 reads).…”
Section: Bacteria With Potential Resistance To Heavy Metalsmentioning
confidence: 49%
“…6 Venn drawing showing the detected bacterial genera found in the three different groups of H, M, and C. Overlaps between the groups are indicated by the arrangement of the circles is tripled in group M. Moreover, Thiobacillus relative abundance had close relationship with Fe content (R 2 =0.691, P<0.05). In addition, most Cyanobacteria can produce extracellular polymeric substances, mainly polysaccharide, which could adsorb heavy metals dispersed in the environment (Pereira et al 2009(Pereira et al , 2011. In this study, Cyanobacteria was a rare group, but its total read abundances in groups H (795 reads) and M (1202 reads) were significantly higher than in group C (92 reads).…”
Section: Bacteria With Potential Resistance To Heavy Metalsmentioning
confidence: 49%
“…PCC 6909 and its sheathless mutant CCY 9612 the effects of the presence of the metal were only observed for concentrations of 10 mg/l and 20 mg/l, respectively [32]. The authors also demonstrated that the RPS of these strains have a high affinity to Pb 2+ what could explain the higher tolerance.…”
Section: Accepted Manuscriptmentioning
confidence: 93%
“…Similar concentrations had also toxic effects in Spirulina platensis-S5 [30] Nostoc punctiforme PCC 73120 cells [31], and Gloeothece sp. PCC 6909 [32]. Cu 2+ is an essential micronutrient that acts as a cofactor for several proteins/enzymes, such as plastocyanin and cytochrome c oxidase, involved in the oxygenic photosynthetic electron transfer chain [33,34].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Active gliding in diatoms is related to the cell's ability to secrete extracellular polymeric substances (Cohn, 2001). On the other hand, excretion of polymeric substances is also involved in resistance mechanisms: by binding the toxicant extracellularly, they contribute to limiting the entrance into the cells and thus lessen toxicity (Pereira et al, 2011). Higher motility (increased VSL and a more linear trajectory) in the metolachlor-exposed EUs with respect to controls could thus highlight both increased escape behavior against toxicants and higher excretion induced by exposure.…”
Section: Time-dose Dependent Impacts On Diatomsmentioning
confidence: 99%